Mutations in the WG and GW motifs of the three RNA silencing suppressors of grapevine fanleaf virus alter their systemic suppression ability and affect virus infectivity - Choi, Jiyeong; Browning, Scottie; Schmitt-Keichinger, Corinne; Fuchs, Marc (Frontiers in Microbiology, 2024)
Viral suppressors of RNA silencing (VSRs) encoded by grapevine fanleaf virus (GFLV), one of the most economically consequential viruses of grapevine (Vitis spp.), were recently identified. GFLV VSRs include the RNA1-encoded protein 1A and the putative helicase protein 1BHel, as well as their fused form (1ABHel). Key characteristics underlying the suppression function of the GFLV VSRs are unknown. In this study, we explored the role of the conserved tryptophan-glycine (WG) motif in protein 1A and glycine-tryptophan (GW) motif in protein 1BHel in their systemic RNA silencing suppression ability by co-infiltrating Nicotiana benthamiana 16c line plants with a GFP silencing construct and a wildtype or a mutant GFLV VSR. Mutating W to alanine (A) in WG of proteins 1A and 1ABHel abolished their ability to induce systemic RNA silencing suppression, limit siRNA accumulation, and downregulate NbAGO2 expression by 1ABHel. This mutation in the GFLV genome resulted in a non-infectious virus. Mutating W to A in GW of proteins 1BHel and 1ABHel reduced their ability to induce RNA silencing suppression and downregulated NbDCL2, NbDCL4, and NbRDR6 expression by 1BHel. This mutation in the GFLV genome delayed infection at the local level and inhibited systemic infection in planta. Double mutations of W to A in WG and GW of protein 1ABHel abolished its ability to induce RNA silencing suppression, limit siRNA accumulation, and downregulate NbAGO2 and NbRDR6 expression. Finally, in silico protein structure prediction indicated that a W to A substitution potentially modifies the structure and physicochemical properties of the three GFLV VSRs. Together, this study provided insights into the specific roles of WG/GW not only in GFLV VSR functions but also in GFLV biology.